Author, Reader, Book : Medieval Authorship in Theory and Practice - Kwakkel, Erik, 1970-; Partridge, Stephen Bradford (Book collections on Project MUSE., 2012)
The broad chronological range within this volume reveals the persistence of literary concerns that remain consistent through different periods, languages, and cultural contexts. Theoretical reflections, case studies from a wide variety of languages, examinations of devotional literature from figures such as Bishop Reginald Pecock, and analyses of works that are more secular in focus, including some by Chaucer and Christine de Pizan, come together in this volume to transcend linguistic and disciplinary boundaries."--Pub. desc.